PENGEMBANGAN MODEL SISTEM PEMERIKSAAN PASIEN KATARAK UNTUK EVALUASI KINERJA - Nur Wachid Adi Prasetya; Sri Kusumadewi (Politeknik Sawunggalih Aji, 2018)
Clinical pathway is a multidisciplinary process that focuses on patient care to produce the best results that havebeen determined. The implementation of clinical pathways ensures that no important aspects of service are forgotten.During the implementation of clinical pathway for cataract disease (non complicated), the management of RSU IslamHarapan Anda need to carry out the evaluation of patient examination conducted by doctors and medical personnelaccording to the clinical pathway. Evaluation results are required at medical committee meetings, as strategicinformation for decision making. Evalution of patient examination that runs still by looking and counting one by oneexamination data that exist in each file of cataract patient to be matched based on clinical pathway, so it takes a longtime and not efficient. Development of models from systems that can provide evaluation results faster, and more precisebased on clinical pathway for cataract patients (non complicated), is needed to help provide information with better speedand quality. Data analyzed and used include medical service data, service class data, pricing group data, patient data,employee data, room data, bed data, service unit data, visitation data, and unit visit data. The system receives medicaldata service input, service unit data, and employee data as checking / visitation data of each service unit performing theexamination, then calculates the inspection status to obtain an inspection evaluation score of each examined patient.System generate patient examination evaluation value as physician performance score, which will be reported tomanagement. Implementation of the system shows that the results of physician performance evaluation in accordancewith the number of inspection actions performed by clinical pathway. The result of validity test shows that all questionitems have r-count value greater than r-table, so it can be said valid. The result of usability test show that the system hasusability test value of 82.51%, and has the predicate